DOSES DE NITROGÊNIO EM CULTIVARES DE TRIGO MULTICOLMOS E SEUS REFLEXOS NA APLICAÇÃO EM ESTÁDIO AVANÇADO - Dambrós, Rodrigo; Battisti, Gabriel K.; Martins, João A. K.; Wagner, Juliano F.; Bosa, Diogo; Silveira, Rafaela B. d.; Becker, Raquel W.; Crestani, Maraísa; Carbonera, Roberto; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo